Algorithms for Large Scale Additive Manufacturing in a Free-Flying Environment - Tauscher, Oliver; Jonckers, Declan; Thakur, Aditya R. (Frontiers in Space Technologies, 2022)
Large scale additive manufacturing (LSAM) refers to the fabrication of structures that exceed the build volume of conventional additive manufacturing setups. This can be used for in-space manufacturing (ISM), facilitating the production of large functional structures in space which cannot fit within the payload fairing of a launcher system. In this paper, a new approach for a continuous fabrication process of structural elements is presented, combining the reach of a free-flying satellite and a robotic arm, utilizing a fused filament fabrication (FFF) 3D-printing setup. A motion planning algorithm was developed which calculates energy-efficient movement trajectories based on a truss design input combined with the movement constraints of the satellite and robotic arm. Using this printing paradigm, a long support-free truss was manufactured. This approach was further elevated by extending the truss structure along the second planar axis, thus facilitating the manufacture of structures larger than generally possible through a layer-by-layer approach. Subsequently, combining the segmented and continuous printing approach, a planar truss structure was produced.